Youth Purchasing Preferences in Rural Areas and Advertising Effects of Celebrity Endorsements - Kirti (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2023)
The modern era of marketing is highly driven by the competitive force which has taken it to a different level. Advertising is one of the basic needs for every organization to promote its products. Celebrities are considered to be one of the major contributors to creating a huge market for a brand and its manufacturers. Being ideal for many, they can influence the perception of the buyers towards a product. Rural consumers comprise a huge population of consumers in India. Their buying decisions are influenced by several factors making it a matter of study. This research aims to investigate how celebrity endorsements in advertising affect the purchasing behavior of young consumers residing in India's rural regions. For this, a study is conducted on young buyers from the rural areas of Punjab.